2010
DOI: 10.1002/hup.1117
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone versus olanzapine for the treatment of delirium

Abstract: Risperidone and olanzapine were equally effective in reducing delirium symptoms. The response to risperidone was poorer in the older age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 27 publications
4
81
0
8
Order By: Relevance
“…Studies comparing haloperidol and risperidone (Han & Kim, 2004;Kim et al, 2005;Liu et al, 2004) have suggested similar efficacy for both medications, with response rates ranging from 58.3 to 75% (haloperidol) and 42 to 77.8% (risperidone). Another study assessing risperidone and olanzapine in the management of delirium found similar response and side-effect rates but concluded that risperidone may result in poorer response rates in older age populations (Kim et al, 2010). More recent studies could not find differences among haloperidol, risperidone, and olanzapine (Grover et al, 2011;Yoon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing haloperidol and risperidone (Han & Kim, 2004;Kim et al, 2005;Liu et al, 2004) have suggested similar efficacy for both medications, with response rates ranging from 58.3 to 75% (haloperidol) and 42 to 77.8% (risperidone). Another study assessing risperidone and olanzapine in the management of delirium found similar response and side-effect rates but concluded that risperidone may result in poorer response rates in older age populations (Kim et al, 2010). More recent studies could not find differences among haloperidol, risperidone, and olanzapine (Grover et al, 2011;Yoon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although some randomized controlled trials are available evaluating the role of various atypical antipsychotics in delirium [5][6][7][8][9][10][11][12][13][14], the data are still limited. These trials have compared an antipsychotic agent with haloperidol [5][6][7][8]10] or two atypical agents [11,14], and only few trials had placebo-controlled design [8,12] for treatment of delirium. One trial compared haloperidol with chlorpromazine and lorazepam [9].…”
Section: Introductionmentioning
confidence: 99%
“…This difference might result from the differing patient population and the setting of the intensive care unit versus the general ward. Other trials comparing the treatment response of atypical antipsychotics based on age (<70 years, ≥ 70 years) suggest that increasing age predict a poor response to delirium treatment in spite of antipsychotic treatment [32,33]. Our data were collected from inpatients aged >65 years, and the mean age of enrolled subjects was 76.2 ± 6.6 years.…”
Section: Discussionmentioning
confidence: 99%